Family support, quality of life and concurrent substance use among methadone maintenance therapy clients in China - Lin, C. (2011)
OBJECTIVES: The methadone maintenance therapy (MMT) programme has been scaled up rapidly in China. This study explored the family support perceived by MMT clients and its association with their quality of life and concurrent illicit drug use. STUDY DESIGN: Cross-sectional study. METHODS: Five hundred and sixty MMT clients were selected at random from 28 MMT clinics and services in Zhejiang and Jiangxi Provinces, China for participation in a face-to-face interview study. The participants’ perceived family support and quality of life were measured through face-to-face structured interviews conducted by trained interviewers. Self-reported information about illicit drug use was obtained from clients. Urine specimens were collected from the participants to test for heroin use. RESULTS: Among the 560 participants, 471 (84.1%) were male and 168 (30.0%) were unemployed at the time of the study. In total, 398 (71.1%) were injecting drug users and 309 (55.2%) had a history of drug use of more than 10 years. Around one-third (n=211, 37.7%) of the participants reported concurrent illicit drug use or had a positive urine test. Perceived family support was associated with increased physical health, psychological health, environmental health and social health. In addition, perceived family support was negatively correlated with concurrent substance use. CONCLUSIONS: Drug use and MMT is a family issue in China. Based on the findings of this study, it is suggested that involving family members in recruitment and interventions of the MMT programme will achieve higher rates of participation and compliance.